1992
DOI: 10.1021/bi00160a022
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the concentration of pre.beta. high-density lipoprotein in normal plasma by cell membranes and lecithin-cholesterol acyltransferase activity

Abstract: A minor fraction of plasma high-density lipoprotein (pre beta-1 HDL) has been shown to promote cholesterol efflux from peripheral cell membranes [Castro, G. R., & Fielding, C. J. (1988) Biochemistry 27, 25-29]. When isolated native plasma is incubated at 37 degrees C, this fraction is specifically decreased. On the other hand, the level of plasma pre beta-1 HDL is fully protected in the presence of even very low levels of fibroblasts, vascular smooth muscle cells, or macrophages. Blood cells were completely in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
72
1
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 28 publications
5
72
1
1
Order By: Relevance
“…However, this effect, which was associated with conversion of pre␤HDL to other HDL particles, is not observed if incubation is performed in the presence of fibroblasts, vascular smooth muscle cells, or macrophages. 23 In Figure 1, it was demonstrated that incubation of plasma with macrophages for various lengths of time (up to 6 hours) does not change its ability to promote subsequent cholesterol efflux from the foam cells during a 30 minutes incubation. This result allowed us to design experiments in which the effect of mast cell granule remnants on the cholesterol efflux-inducing capacity of plasma could be studied for prolonged periods in a system comprising plasma, granule remnants, and macrophages.…”
Section: Effect Of Granule Remnants On 3 H-cholesterol Efflux Promotementioning
confidence: 95%
See 2 more Smart Citations
“…However, this effect, which was associated with conversion of pre␤HDL to other HDL particles, is not observed if incubation is performed in the presence of fibroblasts, vascular smooth muscle cells, or macrophages. 23 In Figure 1, it was demonstrated that incubation of plasma with macrophages for various lengths of time (up to 6 hours) does not change its ability to promote subsequent cholesterol efflux from the foam cells during a 30 minutes incubation. This result allowed us to design experiments in which the effect of mast cell granule remnants on the cholesterol efflux-inducing capacity of plasma could be studied for prolonged periods in a system comprising plasma, granule remnants, and macrophages.…”
Section: Effect Of Granule Remnants On 3 H-cholesterol Efflux Promotementioning
confidence: 95%
“…20,21 They can also be formed when apoA1 is incubated with macrophages, 22 fibroblasts, or vascular smooth muscle cells. 23 These pre␤LpA1 particles are discoidal and remove cholesterol from cells very rapidly by a process that involves interaction with protease-sensitive domains on the cell surface. 24,25 From pre␤ 1 LpA1, cell-derived cholesterol is rapidly transferred to the bulk of ␣-LpA1, presumably by conversion of particles of the former type into those of the latter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular UC acquired by pre-β-HDL eventually appears on the more abundant, α-migrating HDL species, with the concurrent loss of pre-β-HDL species. [4][5][6]10 It is unclear whether this movement of cellular cholesterol from pre-β-HDL species to α-HDL is due solely to transformation (remodeling) of the pre-β particles into α-HDL or if a transfer of cholesterol (shuttling) also occurs. Definitive studies aimed at tracking the flow of UC have been difficult, owing to the low abundance of pre-β particles, which represent <4% of the cholesterol mass in plasma, and to the rapid transformation into α-HDL by the action of lecithinxholesterol acyltransferase in whole serum.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…In one pathway, called the specific pathway, pre 1-HDL interacts with cell membranes and takes up cholesterol via ATP-binding cassette (ABC) A1 expressed on the cell surface. Pre 1-HDL conversion to -HDL is one of the critical steps in this specific RCT and is mediated by lecithin: cholesterol acyltransferase (LCAT) 8) …”
mentioning
confidence: 99%